Pharmacogenetic application in a patient diagnosed with Schizophrenia and OCD: A case report - ULUCAN, KORKUT (My University, 2023)
Introduction:The efficiency of psychiatric therapy depends on various factors and drug metabolism is one of them. The liver plays a significant role in drug metabolism through the P450 enzyme systems. However, pharmacogenetics aims to assist clinicians in determining the effectiveness of a particular drug and minimizing potential side effects.Case report:Here, we present a case to demonstrate the potential use of pharmacogenetics in clinical practice. A 33-year-old male patient with a diagnosis of schizophrenia and OCD had symptoms of sexual auditory hallucinations and obsessive images. According to the patient’s pharmacogenetic profile (CYP2D6, CYP2C9, CYP2C19, CYP1A2andCYP3A4), the medication started by giving Risperidone 8 mg/day and Aripiprazole 5 mg/day. Aripiprazole was continued at 10 mg/day and then 20 mg/day in the presence of clinicalfindings. Olanzapine 10 mg/day and Sertraline 50 mg/day were given. In addition, 20 sessions of TMS and 20 sessions of tDCS, which are neuromodulation treatments, were applied.Results:The patient in question experienced some improvement and partial remission following a treatment plan based on pharmacogenetic analysis. In summary, pharmacogenetic testing can be a valuable tool in determining an appropriate treatment plan that maximizes clinical improvement while minimizing potential adverse effects associated with medication.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)